2012
DOI: 10.1111/j.1471-0528.2011.03229.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV care need not hamper maternity care: a descriptive analysis of integration of services in rural Malawi

Abstract: Objective To evaluate the use of reproductive health care and incidence of paediatric HIV infection during the expansion of antiretroviral therapy and services for the prevention of mother-tochild transmission in rural Malawi, and the influence of integration of these HIV-related services into general health services.Design Descriptive analysis.Setting Thyolo District, with a population of 600 000, an HIV prevalence of 21% and a total fertility rate of 5.7 in 2004.Population Women attending reproductive health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…For example, studies in Indonesia, Malawi, and Ghana have divulged that women who had to pay more in terms of the waiting time and distance to the facility were less likely to utilize maternal care 14,15,27,31. Correspondingly, in most of the health facilities in Africa, mother and baby care are separated 34,35. Therefore, women who have given birth are supposed to go to the facility two or three times within a short period of time for neonatal and postnatal care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies in Indonesia, Malawi, and Ghana have divulged that women who had to pay more in terms of the waiting time and distance to the facility were less likely to utilize maternal care 14,15,27,31. Correspondingly, in most of the health facilities in Africa, mother and baby care are separated 34,35. Therefore, women who have given birth are supposed to go to the facility two or three times within a short period of time for neonatal and postnatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Weak program links, health systems, and financial infrastructure are cited as a prominent barriers to ANC attendance and integrated ANC service delivery (systematically reviewed in [18, 39, 40]). For example, the provision of HIV treatment at specialised ART clinics separate to ANC clinics reduced uptake of HIV services in pregnant women by around 50% [21, 29, 30]. To counter this problem, governments, in conjunction with non-governmental organisations, have begun integrating HIV services and PMTCT into primary healthcare and ANC with the recognition that HIV-specific resources could be allocated diagonally (aiming for disease-specific results through enhanced health systems) [18, 41].…”
Section: Introductionmentioning
confidence: 99%
“…Enablers that have helped overcome identified structural barriers in integrated ANC, reproductive health and primary care services include streamlined funding, effective distribution/logistical systems, integrated health information systems [21, 30, 33, 44], provision of all services on the same site [21, 57], free or low-cost testing and treatment [57], holistic, comprehensive healthcare delivered by multi-skilled health workers or different health workers under the same roof [57], provision of support (psychosocial, financial) to encourage treatment adherence and clinic attendance [57–59], and well-supported trained healthcare staff [33, 42, 49, 6063]. Careful consideration of these enablers in the design and implementation of integrated ANC, HIV, TB and malaria services is required and will generate demand for such integrated services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an evaluation of a PMTCT program in Ethiopia – which uses PMTCT as an entry point to comprehensive, integrated care for the mother, her child and family members – reported high levels of postpartum contraceptive use among PMTCT clients in addition to other relevant PMTCT outcomes [12]. Another study from Malawi found the scale up and integration of PMTCT and ART services into primary care services from 2005 to 2010 were associated with not only a substantial reduction in the proportion of HIV-exposed infants testing positive, but also a 40% increase in family planning consultations [13*]. …”
Section: The Disconnect Between Policy and Practicementioning
confidence: 99%